Effect of Cinnamon Essential Oil on the Chemotherapy-Induced Nausea and Vomiting of Cancer Patients - Shima Mehrabian; Batool Tirgari; Mina Beitollahi; Mansooreh Azizzadeh Forouzi; Behjat Kalantari Khandani (Iranian Journal of Nursing and Midwifery Research)
Background: Despite progress made in antiemetic control, most cancer patients still experience chemotherapy-induced nausea and vomiting. In oncology departments, nurses can evaluate the effects of complementary therapies such as use of essential oil on reducing nausea and vomiting of patients undergoing chemotherapy. Therefore, this study was conducted to explore the effect of cinnamon essential oil on the chemotherapy-induced nausea and vomiting of cancer patients. Materials and Methods: This is a two-group experimental study with a pretest-posttest design that was conducted between January 20 and March 15 of the year 2020. Through convenience sampling, 70 patients experiencing chemotherapy-induced nausea and vomiting were recruited to participate in this study. The participants were randomly allocated to two control and intervention groups. A pad moistened with 2 ml of isotonic saline and 0.2 ml of cinnamon essential oil was first placed inside a plastic bag, and then patients in the intervention group were asked to take three deep breaths while their face was towards the bag for two times at five-minute intervals. Patients in the control group used a placebo (a pad moistened with 2 ml of isotonic saline) instead of cinnamon essential oil during the intervention period. Participants in the two groups received routine antiemetic treatment. Using Visual Analog Scale (VAS), the severity of nausea and vomiting was measured in both groups before the intervention. For this reason, the severity of nausea and vomiting was measured after the first three breaths, and then after the second three breaths. Data were analyzed by SPSS software, using independent t-test, Chi-squared test, and Fisher’s exact test. Repeated measures ANOVA were also used to evaluate nausea and vomiting between the two groups across times. The significant level of 0.05 was considered for all tests. Results: There were no significant differences between the two groups in terms of demographic characteristics and the severity of chemotherapy-induced nausea and vomiting before the intervention. The severity of chemotherapy-induced nausea and vomiting was significantly lower in the cinnamon group than the control group after the first 3.08 (0.55), (F2 = 13.27, p < 0.001) and second breaths 1.91 (0.33) (F2 = 11.39, p < 0.001). Conclusions: Nurses can educate patients and their families to use of cinnamon essential oil. Nursing managers can also emphasize on the use of cinnamon essential oil, which is one of the non-pharmacological, low-cost, and effective methods of reducing chemotherapy-induced nausea and vomiting, by holding in-service training classes.